A Rare Case Of A Trans-Stomal Hernia, Combined With Undiagnosed Mediastinal Lymphadenopathy In A Patient With Rectal Cancer - Kamelia Tsvetanova; Dobromir Dimitrov; Hyuliya Feradova; Vasil Nanev; Tsvetomir Ivanov; Todor Dimitrov (Journal of Biomedical & Clinical Research)
Colon cancer is one of the most common malignant diseases with high grade of malignancy and mortality at high rate. Approximately one million people are diagnosed with colorectal cancer each year. Metastases affect mostly the liver, followed by the lungs. Here is a rare case of a patient with rectal cancer without disease progression or recurrence who underwent surgery due to a trans-stomal hernia, combined with high transstomal fistula of the ileum. Acute respiratory failure developed in the postoperative period and led to fatal deterioration as a result of enlarged metastatic mediastinal lymph nodes, which was very difficult to diagnose.